La formación de la práctica fotográfica en Bogotá 1839-1871, circulación y búsqueda de sentidos (2020)
The practice of photography in Bogotá in the mid-nineteenth century emerged from a network of relationships of subjects (photographers, scientists, merchants, diplomats), objects (machines, chemicals, plates, papers ...) and knowledge (about the techniques and procedures to make the pictures). The mobility of this different elements and the connections between them were part of the DNA of photography in its origins. This work aims to answer the question of what were the mechanisms and relationships that allowed the formation of the practice of photography in the Colombian capital between 1839 and 1871. This research seeks to demonstrate the central role of the circulation and movement of the actors involved in photographic practice and the ways in which these human, material and immaterial actors gave meaning to this activity, through their participation in exhibitions and the execution of technical procedures that generated, not only a physical and visible result in the photographs...